Textural Analyses of the Bar Sands of Gorai River: Implication for Depositional Phase and Environment (Jahangirnagar University Environmental Bulletin, 2013)
DOI: http://dx.doi.org/10.3329/jueb.v1i0.14544 Jahangirnagar University Environmental Bulletin, Vol.1, 25-34, 2012